PENGELOLAAN DATA ANGGOTA BERBASIS WEBSITE DI YAMAHA VIXION CLUB CABANG BANDUNG - Nova Indrayana Yusman (Universitas Maso'em Bandung, 2020)
Yamaha Vixion Club Bandung (YVCB) was formed on July 7, 2007 in the city of Bandung, as a place of friendship between Yamaha Vixion motorcyclists. In its organizational structure, YVCB has a Human Resource Development (HRD) division. Until now, there are more than 800 Yamaha Vixion Club Bandung members. This software is made to facilitate the work of the Yamaha Vixion Club Bandung HRD Division in processing member data. Created using Microsoft Webmatrix as an editor with the PHP programming language. The database uses MySQL with PHPMyAdmin as the software. The method used in making this software is prototyping so that between developers and customers can understand each other what the customer wants. The purpose of making web-based member data management software is that in terms of managing member data it can be done anytime and anywhere by just accessing the internet. In the use of the program, the author chose to use PHP, because PHP is the best and easiest to use in website programming language. Based on the last paragraph, the author intends to make aplication based computerized attendance so that become effective and efficient in terms of time.